Impact of different border crops on growth and yield performance of cauliflower (Brassica oleracea var botrytis L.) varieties - Jayamini, A.G.I.; Pradheeban, L.; Nishanthan, K. (University of Jaffna, 2021)
The use of border crops in cauliflower was an eco-friendly method for the management of pests. The present study was conducted at the Faculty of Agriculture, Kilinochchi from December 2018 to April 2019. The experiment was carried out in a split-plot design with three replicates. Four different borders, such as sunflower (T1 ), lemongrass (T2 ), chrysanthemum (T3 ), and no border (T4 ) were selected as the main plot treatments, and two different cauliflower varieties such as Mareet (V1 ) and White Shot (V2 ) were used as subplot treatments. The cauliflower varieties were planted at the spacing of 60 cm × 45 cm. All the agronomic practices were done according to the recommendations of the Department of Agriculture except plant protection methods. The growth, plant protection measures, and yield parameters were recorded. ANOVA and Duncan’s Multiple Range Test (DMRT) were used for data analysis. There was no interaction effect between the type of border crops and varieties in all measured parameters. The border and the variety were not significant for plant height and the number of leaves per plant. The curd weight, circumference, diameter, total yield, and marketable yield were significantly different among the border crops, while the greater performances were observed in the lemongrass border (T2 ). The varieties of cauliflower showed a non-significant effect on the yield parameters, and the highest was recorded in the white shot variety. Marketable yield and infested yield have significantly (p=0.05) differed among the different border crop treatments and the highest marketable yield was obtained from lemongrass border (T2 ) in both varieties. The plant protection parameters such as the number of damaged leaves per plant and damaged curds significantly differed among the border crops. The highest was recorded in the control (T4 ) treatment in Mareet variety. It can be concluded that lemongrass border and white shot variety can be recommended as the best treatment combination for cauliflower cultivation in the Kilinochchi district of Sri Lanka during the Maha season.
Keywords: Border crops; Cauliflower; Curd; Growth and yield; Plant protection parameters